INSECT PESTS MANAGEMENT OF BT COTTON THROUGH THE MANIPULATION OF DIFFERENT ECO-FRIENDLY TECHNIQUES - Ahmad, N.; Khan, M. H.; Tofique, M.; Rauf, I. (The Nucleus, 2011)
This study was designed to manage insect pests of Bt cotton through the manipulation of different eco-friendly techniques. A perusal of data, based on the overall performance of different treatments reflected that lowest population of jassids (0.29) was observed in bio-control treated Bt cotton followed by bio-control treated conventional cotton (0.41). Mean per leaf population of thrips was found lowest in insecticide treated Bt cotton (0.97) which was statically at par with bi-control treated conventional cotton (0.95), biocontrol treated Bt cotton (1.09) and colour traps treated Bt cotton (1.50). In case of whiteflies, bio-control treated Bt cotton and bio-control treated conventional cotton again proved effective in maintaining the population at lower levels per leaf (0.33 and 0.35 respectively). No bollworms infestation was recorded in transgenic cotton whereas higher attack of the same was observed in the untreated conventional cotton block. The best results were achieved with the application of bio-control agents in combination with Bt cotton resulting in least infestation by insect pests and maximum seed yield of 3657 kg/ha. The population of Chrysoperla carnea was significantly higher in Bt and conventional cotton treated with bio-control agents as compared to the other treatments. The parasitism percentage of Trichogramma chilonis was observed significantly higher in bio-control treated conventional cotton. The studies manifested that combination of bio-control technology with Bt cotton effectively preserves the local beneficial insect fauna indicating its potential to be used as integrated management system against different insect pests of cotton.